John Travolta Saturday night fever - Badham, John; Stigwood, Robert; Paramount Pictures (California : Paramount Pictures, 2006)
John Travolta gives a sensual and intelligent performance as the troubled Tony Manero - Brooklyn paint store clerk by day and undisputed king of the dance floor by night
Title from title screen
Executive producer, Kevin McCormick ; screenplay by Norman Wexler
Cast: John Travolta, Karen Gorney
DVD Format
Dolby Digital
In English with optional English, Thai, Mandarin, Korean or Cantonese subtitles
Keywords: Travolta, John; Dance -- drama